ASSESSMENT ON KNOWLEDGE REGARDING HUMAN PAPILLOMAVIRUS VACCINATION AMONG MAHSA UNIVERSITY STUDENTS - Mazlan, Nadiatul Azra Ahmad; Hui, Ng Xin (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aimed to assess the knowledge of undergraduate students of MAHSA University on human papillomavirus (HPV) vaccination. Methods: The cross-sectional study was conducted using a self-administered questionnaire among 350 local undergraduate students recruited by convenience sampling. The survey was conducted in English and consisted of questions on demographic data and 14 questions on knowledge toward HPV vaccination. Verbal consent was obtained from the participants beforehand, and their participation was voluntary and anonymous. Results: The participants have scored below average (6.09±3.39) for knowledge on HPV vaccines with a significant difference in terms of age, gender, and program of the study. Students from medicine, dentistry, and biomedical science tend to have better mean knowledge score (7.39±2.99) with 25% scored 10 and above. The non-health-care students showed insignificant lower mean knowledge score of 4.17±2.06, respectively. Conclusion: This study has demonstrated moderate level HPV vaccine knowledge toward HPV vaccination among university students with majority posed background of health-related knowledge.